Crystallization and architecture engineering of ZnWO4 for enhanced photoluminescence. Issue 38 (16th September 2020) - Li, Meiting; Wang, Xuejiao; Zhu, Qi; Li, Ji-Guang; Kim, Byung-Nam
Abstract : Crystal engineering of ZnWO4 was achieved with oxalic acid and (NH4 )2 SO4 as modifiers upon hydrothermal reaction, which produced nanorods, microplates and well-organized architectures that clearly show morphology-dependent photoluminescence. Abstract : Oxalic acid (H2 C2 O4 ) and (NH4 )2 SO4 were originally examined as crystallization and architecture directing reagents for the hydrothermal synthesis of ZnWO4, with the pivotal roles of the C2 O4 2− /Zn 2+ ( R ) and SO4 2− /Zn 2+ ( R ′) molar ratios and hydrothermal temperature/duration investigated in detail. It was clearly demonstrated that C2 O4 2− remarkably altered the reaction pathway and suppressed the intrinsic 1D growth of ZnWO4, eventually leading to 2D crystallites with exposed ab planes. (NH4 )2 SO4 further promoted 2D growth and self-assembly of the ZnWO4 crystallites, leading to flower-like architectures of up to ∼2.5 μm sized large microplates. Photoluminescence properties were thoroughly analyzed and discussed for the representative ZnWO4 and (Zn0.98 Eu0.02 )WO4 products after 700 °C calcination to show the importance of crystallite/architecture engineering.